Hey!
To solve this equation, we must first combine similar elements.
Original Equation :3x - 5x + 4 = 10
New Equation {Changed by Combining Similar Elements} :
-2x + 4 = 10
Now that that's done, we'll move onto the second step. Which is to subtract 4 from both sides.
Old Equation :
-2x + 4 = 10
New Equation {Added Subtract Both Sides by 4} :
-2x + 4 - 4 = 10 - 4
Solution {New Equation Solved} :
-2x = 6
Now we divide both sides by two to get our final answer.
Old Equation :
-2x = 6
New Equation {Added Divided Both Sides by -2} :
=
![(6)/(-2)](https://img.qammunity.org/2019/formulas/mathematics/high-school/k0ysg4y7ilcnvnockg61wluiux5omkdqdc.png)
Solution {New Equation Solved} :
x = -3
So, now we know that in the equation 3x - 5x + 4 = 10, x = -3
Hope this helps!
- Lindsey Frazier ♥